High Endemicity and Distinct Phylogenetic Characteristics of Sindbis Virus in Israel. (1st September 2018) - Avizov, Nataly; Zuckerman, Neta; Orshan, Laor; Shalom, Uri; Yeger, Tamar; Vapalahti, Olli; Israely, Tomer; Paran, Nir; Melamed, Sharon; Mendelson, Ella; Lustig, Yaniv
Abstract: Sindbis virus (SINV) is a mosquito-borne Alphavirus responsible for outbreaks of SINV disease, mainly in north Europe. SINV has been isolated from mosquitoes in Israel since the 1980s but SINV disease outbreaks have never been recorded. To gain better understanding of the kinetics of SINV circulation in Israel, 3008 mosquito pools, collected 2004–2006 and 2013–2015, were tested for SINV and phylogenetic analysis was conducted on partially sequenced SINV-positive pools. Results indicate possible expansion of SINV circulation across Israel in 2013–2015 compared to 2004–2006 with 6.35% (191 pools) of total pools positive for SINV RNA. Phylogenetic analysis showed all sequenced Israeli SINV strains belong to genotype I and form, together with SINV sequences from Saudi Arabia, a distinct Middle Eastern cluster. With high endemicity of SINV and as a major crossroads for bird migration between Africa and Eurasia, Israel provides valuable information on SINV dynamics and pathogenicity. Abstract : In this work we demonstrate that Sindbis virus is highly endemic in mosquitoes in Israel and forms, together with strains from Saudi Arabia, a distinct Middle Eastern cluster within genotype I.